Identification and characterization of a novel, low-temperature-active GH8 endo-β-1,4-glucanase exhibiting broad pH stability from Antarctic Glacieibacterium sp. PAMC 29367 - Kim, Do Young; Lee, Yung Mi; Lee, Jong Suk; Kim, Hyangmi; Chung, Chung-Wook (Frontiers in Microbiology, 2025)
Endo-β-1,4-glucanase plays an essential role in the breakdown of cellulosic substances that consist of D-glucose units linked by β-1,4-glycosidic bonds. In this work, the gene encoding a novel extracellular glycoside hydrolase (GH) family 8 endo-β-1,4-glucanase (GluS) from Glacieibacterium sp. PAMC 29367, an Antarctic lichen (Megaspora verrucosa)-associated bacterial species, was identified, cloned, and characterized. The GluS gene (1080-bp) was predicted to express a non-modular endo-β-1,4-glucanase (38,347 Da) that possesses a single catalytic GH8 domain, showing 65.5% amino acid sequence identity with an uncharacterized endoglucanase from Alphaproteobacteria bacterium (GenBank accession number: PZN92894). Recombinant endo-β-1,4-glucanase proteins (rGluS: 39.0 kDa) produced in Escherichia coli BL21 exhibited the highest carboxymethylcellulose (CMC)-degrading activity at pH 5.0 and 40°C, while maintaining over 80% of maximal endo-β-1,4-glucanase activity even at 25°C. Furthermore, the enzyme exhibited notable stability across a broad pH range from 4.5 to 10.0. rGluS activity was greatly stimulated by >1.3-fold in the presence of 1 mM Co2+, whereas it was nearly completely inhibited by 0.5% sodium dodecyl sulfate or 5 mM N-bromosuccinimide. The specific activity (31.1 U mg–1) and kcat/Km (11.02 mg–1 s–1 mL) values of rGluS for CMC were marginally greater than those for barley β-1,3-1,4-glucan, with a specific activity of 28.9 U mg–1 and kcat/Km of 8.79 mg–1 s–1 mL for barley β-1,3-1,4-glucan. The recombinant enzyme demonstrated no detectable biocatalytic activity for p-nitrophenylglucopyranoside, p-nitrophenylcellobioside, D-cellobiose, and D-cellotriose, while it could cleave D-cellotetraose to generate two molecules of D-cellobiose. Moreover, rGluS-mediated degradation of D-cellopentaose led mainly to D-cellobiose production along with D-glucose and D-cellotriose, while its hydrolysis of CMC yielded D-cellotriose as the dominant end product, accompanied by D-glucose, D-cellobiose and D-cellotetraose. The substrate preferences and degradation profiles of rGluS on cellulosic materials supported its classification as a true GH8 endo-acting β-1,4-glucanase without transglycosylation activity. The findings of this study suggest that rGluS represents a novel, highly active, cold-adapted GH8 endo-β-1,4-glucanase exhibiting broad pH stability, and may serve as an effective candidate for low-temperature processing in the food and textile industries.